WHICH TEAM ARE WE, LEAD TEACHER OR BOSS TEACHER? (AN INVESTIGATION OF IN-SERVICE TEACHERS’ THINKING AND DO TOWARD STUDENTS’ BEHAVIOR AND CLASSROOM MANAGEMENT) - Nuronia Cahyaningtyas; Nadia Asma’ (Universitas Muhammadiyah Surakarta, 2020)
Classroom management always be interesting issue to be discussed over years. It grows more interesting to be explored in its relation to the students’ behavior. By conducting a mini case study, the researchers obtained the data mainly by questionnaire and observations. The participant of this study is 23 in-service teachers who have a varied background and teaching experiences. The findings of this research show in detail how the teachers’ thinking toward the students’ behavior and their strategies to manage their classes. It is found out that the participants admitted that their students are mostly having disruptive behavior. However, the findings show that some of the teachers are able to have a proper strategy to deal with those behaviors; yet, they got difficulty to apply the strategies to the field. Conclusively, the obtained data also reveal which participant belongs to lead teacher and boss teacher.